Effect of humic substances on rumen fermentation, nutrient digestibility, methane emissions, and rumen microbiota in beef heifers() - Terry, Stephanie A (J Anim Sci, 2018)
Ruminants play an important role in food security, but there is a growing concern about the impact of cattle on the environment, particularly regarding greenhouse gas emissions. The objective of this study was to examine the effect of humic substances (HS) on rumen fermentation, nutrient digestibility, methane (CH(4)) emissions, and the rumen microbiome of beef heifers fed a barley silage-based diet. The experiment was designed as a replicated 4 × 4 Latin square using 8 ruminally cannulated Angus × Hereford heifers (758 ± 40.7 kg initial BW). Heifers were offered a basal diet consisting of 60% barley silage and 40% concentrate (DM basis) with either 0- (control), 100-, 200- or 300-mg granulated HS/kg BW. Each period was 28 d with 14 d of adaptation. Rumen samples were taken on day 15 at 0, 3, 6, and 12 h postfeeding. Total urine and feces were collected from days 18 to 22. Blood samples were taken on day 22 at 0 and 6 h postfeeding. Between days 26 and 28, heifers were placed in open-circuit respiratory chambers to measure CH(4). Ruminal pH was recorded continuously during the periods of CH(4) measurement using indwelling pH loggers. Intake was similar (P = 0.47) across treatments. Concentration of ammonia-N and counts of rumen protozoa responded quadratically (P = 0.03), where both increased at H100 and then decreased for the H300 treatments. Apparent total tract digestibility of CP (P = 0.04) was linearly increased by HS and total N retention (g/d, % N intake, g/kg BW(0.75)) was improved (P = 0.04) for HS when compared with the control. There was no effect of HS on CH(4) production (g/d; P = 0.83); however, HS decreased the relative abundance of Proteobacteria (P = 0.04) and increased the relative abundance of Synergistetes (P = 0.01) and Euryarchaeota (P = 0.04). Results suggest that HS included at up to 300 mg/kg BW may improve N retention and CP digestibility, but there was no impact on CH(4) production.